Pemikiran Joseph Schacht dalam Studi Hadis Kontemporer di Indonesia - Ade Pahrudin (Diroyah : Jurnal Studi Ilmu Hadis, 2021)
This study aims to determine the influence of Joseph Schacht's orientalist thought on the development of contemporary hadith studies in Indonesia and the response of hadith researchers to his thoughts. This research is a literature study whose data source is an e-paper of religious, scientific journals in Indonesia. This study found 23 e-articles of Indonesian hadith reviewers who responded and studied Schacht's hadith thoughts. If we compare and refer to previous research (Huda, 2018), which shows that there are 36 e-articles in the study of orientalist thought in the study of hadith in Indonesia, Schacht's original thought has exceeded half. This proves that his thoughts have a relatively massive and dominant influence in orientalist studies and hadith studies in Indonesia. The characteristics and responses of Indonesian hadith reviewers to Schacht's thinking are three characteristics; descriptive-comparative (9 articles), descriptive-comparative-negative (8 articles), and descriptive-exploratory (6 articles). The majority of Indonesian hadith researchers compare Schacht's thoughts with his critics, such as Azami and Motzki. Others tend to argue and disagree with Schacht's and Motzki's thoughts). Some do exploration. The shortcoming of hadith reviewers in Indonesia in analyzing and comparing Joseph Schacht's thoughts is the lack of data on some of the writings used as references. In addition, the new theory has not been seen as the result of the synthesis of thoughts between Schacht's thesis anti-thesis of his critics.